Pesticides in the Atmosphere: Distribution, Trends, and Governing Factors Majewski; - Majewski (CRC Press, 2009)
Most people know about the presence and health effects of pesticide residues in the water they drink. However, they may not realize the impact of atmospheric transportation and deposition of pesticides on water quality. Scientific studies of pesticides in various atmospheric matrices (air, rain, snow, aerosols, and fog) provide some of the answers. Pesticides in the Atmosphere focuses on the review and interpretation of direct measurements of pesticides in the environment. An exhaustive compilation, the book examines hundreds of studies in detailed tabular listings, with accompanying maps that include such features as spatial and temporal domain studies, target analytes, detection limits, and compounds detected. Working with the foundation of forty years of scientific studies, the editors synthesize this research to characterize the common threads and main conclusions. They use this information to identify where we need to improve our understanding of pesticides in the atmosphere and their significance to water quality. Pesticides in the Atmosphere serves as a resource, text, and reference to a wide spectrum of scientists, water managers, and students. It includes extensive compilations of references, interpretive analyses and conclusions. For those not familiar with the atmospheric transportation and deposition of pesticides it provides a comprehensive introduction.